Green Synthaesis Nanomaterial Zinc Oxide with Anthocyanin Extract Hylocereus polyrhizus for DSSC Application - Sholikhah, Mar’atus; Cindya Sari, Elok Putri; Ramadhani, Dea Berliana; Kurniawan, Robi (Universitas Negeri Malang, 2023)
Photovoltaic technology as an alternative to dye-sensitized third-generation solar cells is known as Dye-Sensitized Solar Cell (DSSC). DSSC is a device that can convert solar energy into electrical energy. Natural dye is used because it is relatively cheap and environmentally friendly. The type colour commonly used in DSSC are chlorophyll and anthocyanin. In this study the anthocyanin extract Hylocereus polyrhizus was used because it has a high absorption value. Nanoparticles ZnO is used because it has a relatively large energy gap value and can absorb sunlight optimally. The method used in this research is a spin coating, this method uses the procedure of making a thin film on the substrate. The characterizations were carried out using X-ray diffraction (XRD) to determine the crystal size of the ZnO nanoparticles, to know morphology nanoparticle can use scanning electron microscope (SEM), ultraviolet visible (UV-Vis) spectrometerer is used to determine the value of the band gap energy and solar cell simulator test to determine the efficiency value. The XRD result had a crystal size 30.74 nm. The SEM results that the shape of the particles is oval and homogeneous by agglomeration. The band gap value is 3.67 eV. The efficiency in the solar cell simulator test for the DSSC nanomaterial ZnO with anthocyanin extract Hylocereus polyrhizus was 0,29%.